The court jester [videorecording (DVD)] - Kaye, Danny; Johns, Glynis; Lansbury, Angela, 1925-2022; Parker, Cecil, 1897-1971; Frank, Melvin, 1913-1988; Panama, Norman; Schoen, Vic; Fine, Sylvia; Fine, Sylvia; Cahn, Sammy; Cahn, Sammy (Paramount, 2019)
Danny Kaye plays kind-hearted entertainer Hawkins, who disguises himself as the legendary king of jesters, Giacomo. Hawkins infiltrates the court of the evil villain Basil Rathbone, but when a sorceress hypnotizes him, royal chaos ensues. Giacomo now believes he is also an infamous assassin and alternates between his identities at the snap of a finger.